A review-implementations of hyperspectral images technology for food safety and quality - Alias, Aminah; Mohamed Azmin, Nor Fadhillah; Amid, Azura; Ibrahim, Siti Noorjannah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
In recent years, the human consumption of various type of food has been greatly increased in number worldwide. Quality and safety assessments are vital in ensuring these products meet the food law regulations and safe for human consumption. For this purpose, enormous methods are developed and applied in providing thorough results for poultry meat analysis. Currently, hyperspectral imaging (HSI) technology has become well-recognised technique in food safety and quality evaluations. It is an effective technology that known as a rapid, non-invasive and non-destructive method that can be applied for both qualitative and quantitative analyses. This review presents the foundation of HSI technology and its recent implementation of quality assessment on food products. The potential and future growth of this technology is also discussed.